Comparison between heat treated sapwood and heartwood from Pinus pinaster - Esteves, Bruno (2017)
Sapwood and heartwood samples of Pinus pinaster were treated in an oven at 190ºC and 200ºC for 2-6h. Dimensional stability, measured as Anti Shrinking Efficiency (ASE) between 0% and 65% relative humidity, durability against fungi, mechanical resistance (MOE and MOR), hardness and chemical composition were determined for treated and untreated sapwood and heartwood. Radial ASE reached 52% for sapwood and 50% for heartwood while tangential ASE reached 50% and 40% respectively. MOE increased slightly at the beginning of the treatment decreasing afterwards. No significant differences were found between sapwood and heartwood. MOR decreased by 50% and 30% for sapwood and heartwood respectively. A significant increase in durability against Rhodonia placenta was found for both heartwood and sapwood at the higher temperature and for heartwood only at 190º for 4h.